2019
DOI: 10.3390/ijms20194953
|View full text |Cite
|
Sign up to set email alerts
|

Map-Based Functional Analysis of the GhNLP Genes Reveals Their Roles in Enhancing Tolerance to N-Deficiency in Cotton

Abstract: Nitrogen is a key macronutrient needed by plants to boost their production, but the development of cotton genotypes through conventional approaches has hit a bottleneck due to the narrow genetic base of the elite cotton cultivars, due to intensive selection and inbreeding. Based on our previous research, in which the BC2F2 generations developed from two upland cotton genotypes, an abiotic stress-tolerant genotype, G. tomentosum (donor parent) and a highly-susceptible, and a highly-susceptible, but very product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 104 publications
(124 reference statements)
0
11
0
Order By: Relevance
“…TWLPLPR has GRAVY values below 0, which indicates that TWLPLPR is hydrophilic. The positive GRAVY score of YVLLPSPK and KVPPLLY indicates its potential higher hydrophobic residue content . The above results may explain that TWLPLPR seems to have no better effects on GSH-Px activity and the expression of lysosome-related proteins.…”
Section: Resultsmentioning
confidence: 89%
“…TWLPLPR has GRAVY values below 0, which indicates that TWLPLPR is hydrophilic. The positive GRAVY score of YVLLPSPK and KVPPLLY indicates its potential higher hydrophobic residue content . The above results may explain that TWLPLPR seems to have no better effects on GSH-Px activity and the expression of lysosome-related proteins.…”
Section: Resultsmentioning
confidence: 89%
“…miR160 implicates in multiple regulations of biological processes by regulating ARFs . For example, as the main root and floral regulator, miR160 and its ARF targets were proved to involve in heat stress, drought tolerance and N-deficiency stress ( Magwanga et al, 2019 ; Chen et al, 2020 ; Dai et al, 2021 ). By controlling the establishment of the root system architecture of root, the key organ governing water and nutrients uptake, miR160 was able to regulate plants development under N-deficiency condition ( Liang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a nitrogen-starvation responsive gene, miR160 regulated the establishment of root system architecture through the auxin signaling pathway under nitrogen starvation conditions in plants ( Liang et al, 2012 ; Hua et al, 2020 ; Singh and Singh, 2021 ). miR160 could enhance LRs or ARs developments under N-deficiency conditions to maximize the capacity of many plants, such as Arabidopsis , cotton, and B. napus , to uptake the little available nitrogen ( Magwanga et al, 2019 ). In common beans, miR160 was found to be differentially regulated under P-deficiency in different organs.…”
Section: Role Of the Mir160 In The Interaction Of Plants With The Env...mentioning
confidence: 99%
“…NAC TFs not only participate in plant growth and development (such as lateral root development, flower development, secondary wall formation and plant hormone signal transduction) but also play an important regulatory role in plant responses to abiotic stress, such as drought, salinity, water logging and low temperature 37 . Some members of the NAC TF family are critical in enhancing tolerance to N deficiency in cotton 38 . In this study, one NAC TF (ref0030817) was found to perform a regulatory function in the excessive nitrogen stress response.…”
Section: Discussionmentioning
confidence: 99%